Pengembangan APE Rare Hat untuk Meningkatkan Konsentrasi Belajar pada Anak Usia Dini: Development of Rare Hat APE to Increase Learning Concentration in Early Childhood - Meta Orilia Santi Ni Wayan; Septiari Dewi Putu Ayu; Suardika I Komang (Universitas Ngudi Waluyo, 2023)
A PAUD teacher is required to have competence in creativity and innovation in addition to other basic early childhood competencies. Creativity and innovation will move teachers to be able to develop educational game tools (APE) as early childhood learning media. APE Rare Hat is a game tool in the form of a hat which is innovated in such a way as a learning medium. This research aims to develop APE Rare Hat which can be used by children in the learning process. This study used development research methods with the ADDIE model approach including the stages: analysis, design, development, implementation, evaluation. Sources of data on teachers and principals of the State Kindergarten in Jumpai Village, Klungkung. Data collection techniques were carried out by observation and interviews. The research material was analyzed descriptively qualitatively using the theory of child development. The results of the research show that at the stage; analysis found analysis of needs, curriculum and characteristics of children. The design stage is carried out by making a design, the APE development stage is made concretely, the implementation stage gets input from the validator to evaluate material that is not in accordance with the child's age stages. Validation was carried out by 2 learning material experts and 5 learning media experts. The data obtained were analyzed by descriptive qualitative and quantitative analysis using the Aiken's V content validity coefficient technique. From the results of the material expert's assessment using Aiken's V content validity coefficient, a calculated value of 1 (0.99) was obtained. Based on media expert data calculations using Aiken's V content validity coefficient, a value of 0.86 was obtained so that Rare Hat media was declared valid. Based on the results of the study, it can be concluded that Rare Hat media is very suitable for the development of children's ages and is suitable for use as a medium in the learning process in kindergarten. ABSTRAK Seorang guru PAUD dituntut untuk memiliki kompetensi dalam kreativitas dan inovasi selain kompetensi dasar kepaudan lainnya. Kreativitas dan inovasi akan menggerakkan guru untuk dapat mengembangkan alat permainan edukasi (APE) sebagai media belajar PAUD. APE Rare Hat adalah alat permainan berupa topi yang diinovasi sedemkian rupa sebagai media pembelajaran.Penelitian ini bertujuan untuk melakukan pengembangan APE Rare Hat yang bisa diaplikasikan oleh anak pada saat kegiatan pembelajaran. Penelitian ini menggunakan metode penelitian pengembangan dengan pendekatan model ADDIE meliputi tahapan : analisis, perancangan, pengembangan, implementasi, evaluasi. Sumber data guru dan kepala sekolah TK Negeri Desa Jumpai Klungkung. Teknik pengambilan data dilakukan dengan observasi dan wawancara. Bahan penelitian dianalisis secara deskriptif kualitatif dengan menggunakan teori perkembangan anak. Hasil penelitian menunjukan bahwa pada langkah; analisis ditemukan analisis kebutuhan, kurikulum dan karakteristik anak. Tahap perancangan dilakukan dengan pembuatan desain, tahap pengembangan APE dibuat secara nyata, tahap implementasi mendapat masukan dari validator untuk melakukan evaluasi materi yang belum sesuai dengan tahapan usia anak. Validasi dilakukan oleh 2 orang ahli materi pembelajaran dan 5 orang ahli media pembelajaran. Data yang diperoleh dianalisis secara deskriptif kualitatif dan analisis kuantitatif menggunakan teknik koefisien validitas isi Aiken’s V. Dari hasil penilaian ahli materi menggunakan koefisien validitas isi Aiken’s V diperoleh nilai perhitunga sebesar 1(0,99). Berdasarkan perhitungn data ahli media menggunakan koefisien validitas isi Aiken’s V diperoleh nilai sebesar 0,86 sehingga media Rare Hat dinyatakan valid. Berdasarkan hasil penelitian dapat disimpulkan bahwa media Rare Hat sangat sesuai dengan perkembangan usia anak dan layak digunakan sebagai media dalam proses pembelajaran di TK.